Covid-19 Diagnosis Using Deep Learning From X-Ray and CT Images – Overview - Michalska-Ciekańska, Magdalena; Boyko, Oksana (Видавництво Львівської політехніки, 2023)
Since the outbreak of the pandemic in 2019, Covid-19 has become one of the most important topics in the field of medicine. This disease, caused by the SARS- CoV-2 virus, can lead to serious respiratory diseases and other complications. They can even lead to death. In recent years, the number of Covid-19 cases around the world has increased significantly, resulting in the need for rapid and effective diagnosis of the disease. Currently, the use of deep learning in medical diagnostics is becoming more and more common. It provides the high diagnostic efficacy that scientists, doctors and patients care about. During the Covid-19 diagnostic procedure, most clinicians order images from X- ray and CT to be taken from patients. It is the analysis of these images that gives a full diagnosis. In this article, we will discuss the use of deep neural networks in the diagnosis of Covid-19, especially using chest images taken from X-ray and CT.
Keywords: deep learning; convolutional neural networks; Covid-19 diagnostics; CT scans; chest X-ray